2018
DOI: 10.1038/mi.2017.41
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ increases susceptibility to influenza A infection through suppression of group II innate lymphoid cells

Abstract: Increased levels of IFN-γ are routinely observed in the respiratory tract following influenza virus infection, yet its potential role remains unclear. We now demonstrate that influenza-induced IFN-γ restricts protective innate lymphoid cell group II (ILC2) function in the lung following challenge with the pandemic H1N1 A/CA/04/2009 influenza virus. Specifically, IFN-γ deficiency resulted in enhanced ILC2 activity, characterized by increased production of IL-5 and amphiregulin, and improved tissue integrity, ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
143
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(153 citation statements)
references
References 49 publications
10
143
0
Order By: Relevance
“…However, ILC2 might play an important role in regulating the balance between type 1 and type 2 immunopathology consequent to viral infection. Extending previous observations, a recent publication by Califano et al proposed that suppression of ILC2 responses by IFN‐γ actually exacerbate lung injury after high‐dose infection with the pandemic strain H1N1 CA04, by means of reduced levels of IL‐5 and Areg, as well as compromised tissue integrity. Another level of regulation exerted by viral infections on ILC2 responses and immunopathology is possibly related to the ability of pro‐inflammatory cytokines such as IL‐1β, IL‐12, and IL‐18 to promote conversion of ILC2 towards ILC1, a phenomenon which is exacerbated by cigarette smoke .…”
Section: Role Of Ilcs In Lung Infection and Ilc Immunitymentioning
confidence: 74%
“…However, ILC2 might play an important role in regulating the balance between type 1 and type 2 immunopathology consequent to viral infection. Extending previous observations, a recent publication by Califano et al proposed that suppression of ILC2 responses by IFN‐γ actually exacerbate lung injury after high‐dose infection with the pandemic strain H1N1 CA04, by means of reduced levels of IL‐5 and Areg, as well as compromised tissue integrity. Another level of regulation exerted by viral infections on ILC2 responses and immunopathology is possibly related to the ability of pro‐inflammatory cytokines such as IL‐1β, IL‐12, and IL‐18 to promote conversion of ILC2 towards ILC1, a phenomenon which is exacerbated by cigarette smoke .…”
Section: Role Of Ilcs In Lung Infection and Ilc Immunitymentioning
confidence: 74%
“…A recent study showed that genetic IFN-γ deficiency or anti-IFN-γ treatment during IAV infection did not increase ILC2s but enhanced their activity and release of IL-5 and amphiregulin and improved tissue protection without affecting viral load or clearance. 173 These effects were dependent on IL-5 and were not observed in ILC2-deficient mice.…”
Section: Respiratory Syncytial Virusmentioning
confidence: 99%
“…Its role in tissue homeostasis is implied in studies wherein ILC depletion was shown to impact lung function, epithelial integrity and tissue remodeling (92). The high amounts of type I and type II IFNs produced during the early phase of IAV infection have been shown to inhibit ILC2 function and proliferation (94). Conversely, IFN-γ deficiency leads to host protection through increased production of IL-5 and amphiregulin by ILC2 (94).…”
Section: Epithelial-resident Leukocyte Crosstalk During Early Iav Infmentioning
confidence: 99%
“…The high amounts of type I and type II IFNs produced during the early phase of IAV infection have been shown to inhibit ILC2 function and proliferation (94). Conversely, IFN-γ deficiency leads to host protection through increased production of IL-5 and amphiregulin by ILC2 (94). Both NKT-cells and AMs have also been shown to produce IL-33 in response to IAV signaling ILCs to produce IL-5 (95), and increased levels of IL-5 during the viral clearance phase may help recruit eosinophils to the airway mucosal barrier (95) which can enhance cellular immune responses (96) and perhaps necessary for tissue repair (97).…”
Section: Epithelial-resident Leukocyte Crosstalk During Early Iav Infmentioning
confidence: 99%